2011
DOI: 10.1016/j.nbt.2011.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Lipase from marine Aspergillus awamori BTMFW032: Production, partial purification and application in oil effluent treatment

Abstract: Marine fungus BTMFW032, isolated from seawater and identified as Aspergillus awamori, was observed to produce an extracellular lipase, which could reduce 92% fat and oil content in the effluent laden with oil. In this study, medium for lipase production under submerged fermentation was optimized statistically employing response surface method toward maximal enzyme production. Medium with soyabean meal-0.77% (w/v); (NH(4))(2)SO(4)-0.1m; KH(2)PO(4)-0.05 m; rice bran oil-2% (v/v); CaCl(2)-0.05 m; PEG 6000-0.05% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 58 publications
0
42
0
4
Order By: Relevance
“…PB, in combination with RSM, has resulted in optimizing the medium and increasing the enzyme yield from a multitude of yeasts, fungi, and bacteria. Rhizopus delemar (Acıkel et al 2010), A. carneus (Kaushik et al 2006), Aspergillus awamori (Basheer et al 2011), Geotrichum sp. (Burkert et al 2004), C. cylindracea (Salihu et al 2011), Burkholderia sp.…”
Section: The Use Of Statistical Tools For Optimizing Lipase Productionmentioning
confidence: 99%
“…PB, in combination with RSM, has resulted in optimizing the medium and increasing the enzyme yield from a multitude of yeasts, fungi, and bacteria. Rhizopus delemar (Acıkel et al 2010), A. carneus (Kaushik et al 2006), Aspergillus awamori (Basheer et al 2011), Geotrichum sp. (Burkert et al 2004), C. cylindracea (Salihu et al 2011), Burkholderia sp.…”
Section: The Use Of Statistical Tools For Optimizing Lipase Productionmentioning
confidence: 99%
“…The crude enzyme extract obtained after SmF was purified by (NH 4 ) 2 SO 4 precipitation (20-90 %), followed by dialysis; and ion-exchange chromatography (Basheer et al 2011). The precipitated protein was resuspended in 50 mM Tris-HCl buffer (pH 8), dialysed against 0.01 M solution of the same buffer for 24 h, at 4°C, and assayed for lipase activity and protein content.…”
Section: Purification Of B Smithii Lipasementioning
confidence: 99%
“…Enzyme characterization by SDS-PAGE and Zymography was performed by the procedures outlined by Basheer et al (2011). Samples precipitated with (NH 4 ) 2 SO 4 and active fractions collected after ion exchange chromatography, were electrophoresed by Native-PAGE and SDS-PAGE in a 10 % polyacrylamide gel according to the method of Laemmli (1970).…”
Section: Sds-page and Zymographymentioning
confidence: 99%
“…The SEM analysis evidenced the A. awamori KM434331 colonies with conidiophores, conidial heads, globose to sub-globose, conidia covering the whole surface of the conidiophore which were similar to that of pathogenic fungi A. awamori BTMFW032 (Beena et al, 2010 and the identity of phylogenetic results showed 100% sequence similarity with the previously available sequences of A. awamori (Basheer et al, 2011).…”
Section: Discussionmentioning
confidence: 54%